Art ± Education: The Paradox of the Ventriloquist's Soliloquy - John Baldacchino (Universidade de Lisboa, 2015)
When we speak of art education, are we trying to make sense of somethingby means of something else, just as a ventriloquist speaks with the mouth ofa dummy to make us believe that he is having a dialogue with someone elsewhen in effect he is speaking to himself? This paper discusses how art educationcould only flourish as an act of approximation as it rejects the incrementaland constructivist assumptions that have turned art and educationinto transactional instruments. Discussing art and education's immanentrelationship, this paper argues that art education is only necessary by forceof the accidents that characterise it. Four scenarios, here identified in whatthe author calls the paradox of the ventriloquist's soliloquy in art education,illustrate this argument. In discussing how this comes about, this papermakes reference to Herner Saeverot's concept of indirect pedagogy andCharles Garoian's prosthetic pedagogy.